2017
DOI: 10.1038/s41598-017-11578-2
|View full text |Cite
|
Sign up to set email alerts
|

Emotion perception improvement following high frequency transcranial random noise stimulation of the inferior frontal cortex

Abstract: Facial emotion perception plays a key role in interpersonal communication and is a precursor for a variety of socio-cognitive abilities. One brain region thought to support emotion perception is the inferior frontal cortex (IFC). The current study aimed to examine whether modulating neural activity in the IFC using high frequency transcranial random noise stimulation (tRNS) could enhance emotion perception abilities. In Experiment 1, participants received either tRNS to IFC or sham stimulation prior to complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 38 publications
3
47
1
1
Order By: Relevance
“…In line with this proposal, neuroimaging techniques have shown that (pre)motor and somatosensory regions representing the face are active during the perception of emotional face [32][33][34][35], and neural activity in these regions correlates with the degree of facial mimicry [36][37][38]. Moreover, damage to, or transcranial magnetic stimulation (TMS) interference with, the face representations in motor and somatosensory areas disrupts facial mimicry and impairs the recognition and interpretation of emotional expressions [39][40][41][42][43][44] (see also [45]). Furthermore, sensorimotor simulation would in turn affect theory of mind and emotion-related regions including the amygdala and the insula [31], especially for dynamic emotional stimuli [46,47].…”
Section: Introductionmentioning
confidence: 90%
“…In line with this proposal, neuroimaging techniques have shown that (pre)motor and somatosensory regions representing the face are active during the perception of emotional face [32][33][34][35], and neural activity in these regions correlates with the degree of facial mimicry [36][37][38]. Moreover, damage to, or transcranial magnetic stimulation (TMS) interference with, the face representations in motor and somatosensory areas disrupts facial mimicry and impairs the recognition and interpretation of emotional expressions [39][40][41][42][43][44] (see also [45]). Furthermore, sensorimotor simulation would in turn affect theory of mind and emotion-related regions including the amygdala and the insula [31], especially for dynamic emotional stimuli [46,47].…”
Section: Introductionmentioning
confidence: 90%
“…These baseline differences in brain state may then interact with the effects of stimulation. Several studies using non-invasive brain stimulation have shown that baseline performance can predict the magnitude of change in performance following tES (e.g., Tseng et al, 2012 , 2018 ; Hsu et al, 2014 , 2016 ; Krause and Cohen Kadosh, 2014 ; Benwell et al, 2015 ; Fertonani and Miniussi, 2017 ; Penton et al, 2017 ). It has been suggested that this may be due to differential recruitment of brain networks/brain state in high and low performers ( Tseng et al, 2012 ; Krause and Cohen Kadosh, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…A final further consideration of our results is the choice of stimulation parameters used. While prior work has shown that the use of bilateral electrode montages for tRNS stimulation can modulate performance in cognitive and perceptual domains (e.g., Cappelletti et al, 2013 ; Snowball et al, 2013 ; Joos et al, 2015 ; Romanska et al, 2015 ; Campana et al, 2016 ; Popescu et al, 2016 ; van der Groen and Wenderoth, 2016 ; van Koningsbruggen et al, 2016 ; Looi et al, 2017 ; Penton et al, 2017 ; Yang and Banissy, 2017 ), recent work using bilateral electrode montages for tRNS to stimulate the motor system has found that this approach does not induce the classical excitatory effects of unilateral tRNS ( Parkin et al, 2018 ). This is similar to studies of transcranial direct current stimulation (tDCS: a more commonly used transcranial electrical brain stimulation technique), where many studies find behavioral differences using bilateral electrode montages, but work using bilateral tDCS montages to modulate activity in the motor system has found mixed results on motor cortex excitability changes (e.g., Nitsche and Paulus, 2000 ; Mordillo-Mateos et al, 2012 ; Sehm et al, 2013 ; Parkin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their greater sensitivity, a major benefit of learning paradigms is that they are closer to those used with impaired populations, which may lead to further developments relevant to neurorehabilitation. Finally, investigations with potentially more effective electrical waveforms, such as transcranial random noise stimulation (tRNS) or transcranial alternating current stimulation (tACS) may prove fruitful for the modulation of higher order cognition in younger adults (e.g., Paulus, 2011 ; Snowball et al, 2013 ; Romanska et al, 2015 ; Penton et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%